Java 1.1 developer's handbook - Heller, Philip (Sybex, 1997)
Learn what's new in JDK 1.1. With extensive coverage of all recently added features, this book gives you up-to-the-minute knowledge of the evolving Java environment. Learn about JDK 1.1's new event-handling paradigm and a number of new APIs designed to enable a wide range of increased functionality, including distributed objects, security, electronic commerce, JavaBeans, and database connectivity. Master the most valuable techniques. Real-world examples on the enclosed CD give you a practical, hands-on workout in all the key topics covered in the book. These applets provide you with the chance to experiment with specific Java techniques. You'll be able to adjust settings and values, click on a button, and see the results. You will be able to clearly understand the critical development operations needed to create an impressive array of functionality.